2010
DOI: 10.1111/j.1439-0507.2010.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans growth and germ tube formation can be inhibited by simple diphenyl diselenides [(PhSe)2, (MeOPhSe)2, (p-Cl-PhSe)2, (F3CPhSe)2] and diphenyl ditelluride

Abstract: Candida species are the fourth most common cause of nosocomial bloodstream infections. An increase in the frequency of infections, which have become refractory to standard antifungal therapy, has been observed. Recent studies have shown that the pro-oxidant properties of diphenyl diselenide (PhSe)(2), a structurally simple organoselenium compound, can be toxic to yeast. The objective of this work was to study, under non-reactive oxygen species (ROS)-generating conditions, the effect of different organochalcoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
(96 reference statements)
0
10
0
Order By: Relevance
“…The probable lack of inhibitory effect of the majority of compounds tested might be due to the fact that the antifungal activity of diphenyl diselenides is dependent on the presence of functional groups [ 40 ]. However, diphenyl diselenides may still display high activity in reducing germ tube formation, one of the crucial virulent factors of C. albicans [ 38 ]. Azoles (ketoconazole and itraconazole), commonly used in antifungal therapy, also did not show activity under the test conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probable lack of inhibitory effect of the majority of compounds tested might be due to the fact that the antifungal activity of diphenyl diselenides is dependent on the presence of functional groups [ 40 ]. However, diphenyl diselenides may still display high activity in reducing germ tube formation, one of the crucial virulent factors of C. albicans [ 38 ]. Azoles (ketoconazole and itraconazole), commonly used in antifungal therapy, also did not show activity under the test conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of biological applications, organoselenium compounds have received particular attention as glutathione peroxidase (GPx) mimics [ 9 , 11 , 14 , 24 ], antioxidant, and anti-inflammatory agents [ 10 , 11 , 13 , 23 ]. Furthermore, a number of selenium-containing compounds have been studied as anticancer [ 12 , 22 , 25 ], anti-angiogenic [ 26 ], antiviral [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], antimicrobial [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], and antileishmanial agents [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro-oxidant effect of the organochalcogenide compound (PhSe) 2 , producing toxic effects on yeast has been demonstrated [33,35]. Recently, it was demonstrated the ability of the organochalcogenide compound (PhSe) 2 to inhibit both growth and germ tube formation by C. albicans [37]. This is an important feature, because the germ tube formation is an essential stage to virulence of C. albicans in animal models of mucosal and systemic infections [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is a very interesting feature that, while (PhSe) 2 has an antioxidant effect, which produce a neuroprotective effect in rats, it can, also, present pro-oxidant properties in different biological systems [36]. Recently, we have demonstrated that different organochalcogenides inhibited both growth and germ tube formation in C. albicans [37]. Accordingly, the antifungal effect of different organochalcogenide compounds against pathogenic fungi was, recently, described [38].…”
Section: Introductionmentioning
confidence: 99%